The dark side of European integration : social foundations and cultural determinants of the rise of radical right movements in contemporary Europe - Polyakova, Alina (Explorations of the far right, 2015)
Based on detailed analysis of the electoral rise of radical right parties, argues that the rising nationalism and the mobilization of the radical right in contemporary Europe are the result of European economic integration, which has produced a cultural backlash